PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN NASABAH DALAM MENGAMBIL PEMBIAYAAN PADA PT BPRS INSAN MADANI KARTASURA SUKOHARJO TAHUN 2017 - Surani, Sri (El-Hayah, 2017)
Abstract : The purpose of this research were to know influence of: 1) the promotion to customer decision in taking financing; 2) the service quality to customer decision in taking financing; 3) the promotion and service quality to customer decision in taking financing at PT BPRS Insan Madani Kartasura Sukoharjo Year 2017.This research used associative quantitative method. This research was conducted at PT BPRS Insan Madani Kartasura Sukoharjo in May - June 2017. The population of this research was financing customer of PT BPRS Insan Madani Kartasura of 182 customers. A sample of 65 respondents taken with simple random sampling technique. Data collection used questionnaires. Technical analysis of data using multiple regression, F test, t test and test of determination. Before analyzing the data, the prerequisite test of classical assumption was test of normality, multicollinearity test, and heteroskedatisitas test.The results of this research were: 1) Promotion (X1) has a t value of 2.645 with a Sig value of 0.048, Sig value smaller than 0.05 indicated that the test was significant, this mean promotion (X1) affects the customer's decision to take the financing Y); 2) the quality of service (X2) has a value of 9.267 with the Sig value of 0.000, the Sig value smaller than 0.05 indicated that the test was significant, it means the service quality (X2) affects the customer's decision to take the financing (Y); 3) The result of analysis was calculated F value 4.510 with Sig 0.000 value so that Sig value is smaller 0,05 hence it was concluded that promotion variable (X1) and service quality (X2) have significant effect to customer decision in taking financing (Y) in BPRS Insan Madani Kartasura Sukoharjo; Result of determination test of R2 obtained value 0,953 mean 95,3% promotion and service quality have positive effect to customer decision in taking financing, the rest equal to 4,7% influenced by other variable outside of research. Keywords: promotion, service quality, customer decision in taking financing